Pengembangan Media Pembelajaran Kincir Misteri Berbasis Local Wisdom Sumatera Selatan Pada Mata Pelajaran IPAS Kelas IV di SD Negeri 223 Palembang - Desti Niwarni; Lian, Bukman; Aryaningrum, Kiki (Universitas Muhammadiyah Kuningan, 2025)
This study reviews the application of various innovative learning models in the context of 21st century education in Indonesia, with a focus on the application of Technological Pedagogical Content Knowledge (TPACK) and other cooperative learning methods. This study refers to the latest research (2020-2024) which examines the effectiveness of implementing TPACK in the Teacher Professional Education (PPG) program, Classroom Action Research (PTK) training oriented towards 21st century learning, as well as the use of creative digital learning media. like a webtoon comic. The method used in this research is a literature review study, by collecting and analyzing scientific articles related to the implementation of PTK in elementary schools. The data collection technique used is analysis, which will later function to collect relevant data and sources in this research. The type of data used is qualitative, chosen because the method applied is a literature study. The results of this study show that the application of TPACK and other innovative learning methods has a positive impact in increasing teacher competence, student interest and involvement, as well as student learning outcomes. Technology-based learning models such as TPACK and Problem Based Learning (PBL) strategies combined with the Talking Stick method, have been proven to be able to improve students' critical thinking skills and activity in learning. This study concludes that collaboration between technology and pedagogy in learning has an important role in building an education system that is responsive to the demands and challenges of the digital era.